The effect of beinaglutide as an glucagon-like peptide-1 receptor agonists on cardiometabolic factors: a systematic review and meta-analysis - Yan Xu; Periyannan Velu; Li Hu; Nathalia Sernizon Guimarães (Diabetology & Metabolic Syndrome)
Abstract Background Considering the important role of cardiometabolic risk factors in different societies on increasing the burden of non-communicable diseases, in this study we will investigate the possible effects of Beinaglutide as an glucagon-like peptide-1 receptor agonists (GLP-1RAs) on these risk factors. Methods In order to identify all randomized controlled trials that investigated the effects of Beinaglutide on cardiometabolic factors, a systematic search was conducted in the original databases using predefined keywords until July 2024. The pooled weighted mean difference and 95% confidence intervals were computed using the random-effects model. Results A quantitative meta-analysis results from 7 studies with 872 participants showed that Beinaglutide has a significant lowering effect on weight (WMD: -3.74 kg; 95% CI: -5.03, -2.45), body mass index (BMI) (WMD:-1.64 kg/m2; 95% CI: -2.10, -1.17), waist circumference (WC) (WMD: -3.19 cm; 95% CI: -4.65 to -1.73), triglycerid (TG) levels (WMD: -0.14 mmol/l with; 95% CI: -0.25, -0.04), and systolic blood pressure (SBP) (WMD: -1.76 mm/Hg; 95% CI: -2.61, -0.91). Furthermore, the results obtain from subgroup analysis showed a greater effect of Beinaglutide on the reduction of weight and TG during the intervention of more than 12 weeks. In addition, body weight loss was greater in doses less than 0.4 mg compared to doses greater than or equal to 0.4 mg. Conclusions The results of this meta-analysis show that Beinaglutide is effective in reducing factors related to obesity, TG as wll as SBP, especially with longer interventions and lower doses.